Dengue fever with bilateral thalamic diffusion restriction lesions: a case report - Husna Yoosuf; Josef A. Alawneh; Zafar Hashim; Umama B. Fatima; Saqib I. Dara (BMC Neurology)
Abstract Background Dengue encephalitis is a rare complication of dengue and can manifest as ischemic stroke, making the diagnosis challenging. This case highlights the need of recognizing unusual presentation of dengue and the use of neuroradiology in its diagnosis. Case presentation A previously healthy 38-years-old man presented to the emergency department with weakness of the left upper limb and bilateral lower limbs, aphasia and confusion. He had flu-like symptoms along with fever for the past 3 days. Magnetic Resonance Imaging (MRI) of the brain showed hyperintensities in the bilateral thalamic and parafalcine regions. The patient was started on aspirin for the suspicion of ischemic stroke. But the patient’s condition deteriorated. Lumbar puncture did not reveal any evidence of meningitis. The blood Reverse Transcription Polymerase Chain Reaction (RT-PCR) confirmed the diagnosis of dengue hemorrhagic fever. Conclusions This article emphasizes the importance of including the complications and manifestations of dengue fever in the differential diagnosis of ischemic stroke in a relevant context. Unique radiological finding of bilateral thalamic lesions can serve as important diagnostic clues in such atypical cases. Early diagnosis can help guide therapy.